Climate and glacier fluctuations in the Bavarian Alps in the past 120 years - Hagg, Wilfried; Mayer, Christoph; Mayr, Elisabeth; Heilig, Achim (ERDKUNDE, 2012)
Five small glaciers in the Bavarian Alps have been surveyed repeatedly since the late 19th century. This enables the calculation of geodetic glacier mass balances, which are known to be key indicators for climate fluctuations. In this paper, the record is extended by the analysis of additional historical maps and by a new survey of the glacier surfaces in 2009/2010. After the 1960s and 1970s, when positive mass balances could be observed, the glaciers experienced severe mass losses, which is consistent with observations from the vast majority of mountain glaciers worldwide. Although the glaciers show individual behaviour which can be explained by topographic peculiarities, the overall trend is an intensified surface lowering during the past decades. To identify the local causes and triggers, homogenized climate data from stations near the glaciers have been analyzed. All records show an extensive warming in summer, but no increase over the altitudinal gradient. Winter precipitation shows little variation on a decadal time scale and reveals no significant trends over time. An analysis of snow height and winter precipitation measurements at Zugspitze proved that the precipitation measurements are not capable to explain glacier behaviour due to gauge undercatch and redistribution of snow by wind. Correlations between geodetically derived glacier mass balances and mean seasonal meteorological conditions indicate that mass losses are mainly caused by increased summer air temperatures. However, mean seasonal values cannot take into account fluctuations of the temporary snow line, which are crucial for the mass balance of small glaciers and which can only be considered using a daily time-step model.